In vitro Evaluation of the Effect of Using Different Gelling agents on the Release of Erythromycin from a Nanocubosomal gel - Sadeq Jaafar Al-Sakini; Nidhal K. Maraie (College of Pharmacy / Mustansiriyah University, 2019)
Preparation of a topical gel for erythromycin using optimized nano-sized cubosome dispersion, which is changed into a gel to get nanocubosomal gel using different  gelling agents. The optimum nanocubosomal dispersion  containing 4.4% glyceryl mono oleate (GMO) (as an oil phase) and 0.6% poloxamer 407 (as an emulsifying agent) was converted into a gel using different gelling agents including carbopol 974, carbopol 940, carbopol 934 and hydroxyl propyl methylcellulose (HPMC) at different ratios of (1:1 and 1:2). Each prepared gel was then evaluated in vitro to determine the homogenisity, consistency, spreadability, viscosity and drug release. The selected formula (FG6) showed best homogenisity, consistency and spreadability as well as it produced initial burst release of 60.3% (within 1 hour) followed by prolonged release of 96.3% continued for 4 hours. In addition, the optimum gel formula (FG6) has shown remarkable antibacterial activity, which was significantly higher than the marketed gel (ERYTHROMYCIN GEL ® 2%) against four different strains of bacteria (Staphylococcus aureus, Klebsiella pneumoniae, Escherichia coli and Pseudomonas aeruginosa).